Plant medicine metabolite Yulinzhu treating neurological disorder causing polycystic ovary syndrome: a systematic review and a meta-analysis - Jiao, Beibei; Chen, Ruilin; Chen, Si; Zhang, Jian; Wang, Peijuan; Zhou, Huaijun; Zhao, Weibo (Frontiers in Pharmacology, 2024)
Background: Polycystic Ovary Syndrome (PCOS) is a prevalent endocrine disorder that affects women of reproductive age, characterized by chronic anovulation, hyperandrogenism, and polycystic ovarian morphology. Emerging evidence indicates that neurological disorders play a significant role in the etiology of PCOS, highlighting the complex interplay between the central nervous system (CNS) and ovarian function. Yulinzhu, a traditional Chinese medicine (TCM) formulation, has been traditionally used to regulate menstrual cycles and improve fertility. This study aims to investigate the efficacy and mechanisms of Yulinzhu in treating PCOS induced by neurological disorders.Methods: An extensive literature search was performed across electronic databases such as PubMed, EMBASE, Cochrane Library, and CNKI, covering publications up to June 1st, 2024. The review included randomized controlled trials (RCTs) that compared Yulin Zhu with placebo, standard care, or other active treatments in patients with PCOS. Two reviewers independently carried out data extraction and quality assessment. Meta-analyses were conducted using both fixed and random-effects models, with heterogeneity evaluated using the I² statistic.We screened 891 records and included 6 studies in the meta-analysis. The meta-analysis revealed that Yulinzhu about effective rate(RR = 1.19, 95% CI [1.10, 1.29], P < 0.0001), pregnancy rate (RR = 2.80, 95% CI [1.65,4.76], P < 0.0001) and ovulation rate (RR = 1.33, 95% CI [1.10, 1.62]], P = 0.04). Meta-analysis shows the results of follicle estrogen (WMD = 0.69, 95% CI [-0.39, 1.78], P = 0.21), luteinizing hormone (WMD = -2.27, 95% CI [-3.86, -0.67], P = 0.005), testosterone (WMD = -0.44, 95% CI [-0.64, -0.25], P＜0.0001), estradiol (WMD = 16.20, 95% CI [2.74,29.67], P＜0.0001).This study demonstrates that plant medicine compund Yulinzhu can may effectively treats PCOS including hormonal regulation, anti-inflammatory actions, and neuroprotection. We expect further research with larger, well-designed clinical trials to substantiate our conclusions.